Damage Assessment of Laboratory-Scale Reinforced Concrete Columns Under Localized Blast Loading - Mohamed Ben Rhouma; Azer Maazoun; Aldjabar Aminou; Bachir Belkassem; Tine Tysmans; David Lecompte (Buildings)
Reinforced concrete (RC) columns are structural components that carry loads and are vulnerable to damage and possible failure under blast loads. Understanding how damage accumulates and cracks propagate in these structural members is essential for improving their resilience and designing blast-resistant buildings. This study introduces an experimental approach to mitigate the fireball and fumes generated by an explosion, allowing for a more precise structural response assessment. With the help of high-speed cameras, this study experimentally investigates the real-time damage progression and crack formation in RC columns. To explore these failure mechanisms, laboratory-scale RC columns with a low reinforcement ratio are intentionally designed to experience significant damage, providing deeper insights into concrete-specific failure patterns. The tested columns are 1800 mm long and have a 100 mm diameter. Each specimen is reinforced with 3 mm longitudinal reinforcement bars and 2 mm transverse bars. An explosive driven shock tube (EDST) is used to apply blast loads, targeting the mid-height of the columns. High-speed digital image correlation (DIC) tracks the overall structural response. A numerical simulation is developed in LS-DYNA and compared with experimental data for validation. The findings demonstrate that the proposed FE model accurately simulates both the applied blast load and the resulting failure patterns. The difference between the mid-span lateral displacement predicted by the numerical simulation and the average experimental measurements remains within 15%.